The effects of globalisation on the performance of labour-intensive industries from southern Europe: the role of localised capabilities - Cesário, M. (2012)
This paper focus on the examination of the competitive positioning of textiles, clothes and leather (TCL) sectors, in the actual context of integration within Europe. The first aim of the paper is to empirically confirm the relation between the strong competition from emerging market economies and the regional job loss in these sectors. Secondly, we argue that localised capabilities are important factors for the economic resilience of TCL firms in the global economy. Using clustering analysis, a set of 13 Southern European Nuts 2 regions was selected because of their strong specialization on TCL industries. For the selected regions, data on the evolution of TCL trade balance was compared with performance indicators (firm density, employment and investment per capita in TCL). The results allow to examine the relationship between the liberalisation process and the evolution of job loss and disinvestment, in regions whose economic tissues are not able to provide employment alternatives.